Describing my Own Experience of Learning Languages (Texas Journal of Philology, Culture and History, 2023)
This article discusses the process of learning foreign languages from my own experience: If we stared the learning process and materials, that are implemented during the lesson, they were all prepared according to our level and became tougher step by step, when we passed the higher level. Texts were all taken from the magazines and journals, that were published in Europe, which means all of the texts were authentic materials for improving the learners’ knowledge. After learning the basic grammar rules, it started to seem easier to acquire and my self- confidence went up every day